2013
DOI: 10.5455/ijmsph.2013.020820131
|View full text |Cite
|
Sign up to set email alerts
|

Use of antimicrobial prophylaxis in clean elective orthopedic surgical procedures and identifying common infective organisms

Abstract: Background: Prophylactic antimicrobials have an important adjuvant role in the prevention of Surgical Site Infection (SSI), which is one of the most preventable causes of post-operative complication. In India, due to lack of adequate information and guidelines for antimicrobial prophylaxis in surgery there is a need to generate baseline data on the pattern of use of prophylactic antimicrobials. Aims & Objective: This study is aimed to analyze the pattern of surgical chemoprophylaxis and surgical site infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Other studies also pointed out that prolonged postoperative antimicrobial prophylaxis doesn’t provide any supplementary benefit and indicated that drug resistant pathogens were noted in prolonged prophylaxis [ 2 , 31 ]. In the face of this, 180 (96%) patients received postoperative antimicrobial prophylaxis for more than 24 h after surgery in the Orthopaedics and Traumatology Surgical Unit, akin to numerous studies which reported prolonged postoperative antimicrobial administration [ 1 , 8 , 10 , 31 , 32 ] and study in Gonder University Hospital where duration of surgical prophylaxis was 3–5 days [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies also pointed out that prolonged postoperative antimicrobial prophylaxis doesn’t provide any supplementary benefit and indicated that drug resistant pathogens were noted in prolonged prophylaxis [ 2 , 31 ]. In the face of this, 180 (96%) patients received postoperative antimicrobial prophylaxis for more than 24 h after surgery in the Orthopaedics and Traumatology Surgical Unit, akin to numerous studies which reported prolonged postoperative antimicrobial administration [ 1 , 8 , 10 , 31 , 32 ] and study in Gonder University Hospital where duration of surgical prophylaxis was 3–5 days [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobials are valued 20–30% of hospital pharmacy budget [ 7 ] and nearly 30–50% of these antimicrobials are given for SAP [ 5 ]. Yet, 30–90% of these SAPs are inappropriate; most antimicrobials are either given at the wrong time, wrong dosage and wrong strength which results in increased antibiotic usage, increased costs, prolonged hospitalization, super infection, and antimicrobial resistance [ 5 , 8 , 9 ]. Moreover, SAP protocols should be revised, as cost of antimicrobials and resistance change [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cefadroxil is given in a single dose of 1 g per day or divided doses of 2 x 500 mg. Meanwhile, for children, the dose is 30 mg/kg in a single or 2 divided doses and is usually used for five days of treatment (Sharon, 2007;Mistry, 2013). (Sharon, 2007), (Mistry, 2013) Cefixime was the second choice of antibiotic for oral use after surgery in this study (table 4).…”
Section: Postoperative Prophylactic Antibioticsmentioning
confidence: 94%
“…Meanwhile, for children, the dose is 30 mg/kg in a single or 2 divided doses and is usually used for five days of treatment (Sharon, 2007;Mistry, 2013). (Sharon, 2007), (Mistry, 2013) Cefixime was the second choice of antibiotic for oral use after surgery in this study (table 4). Cefixime is a third-generation cephalosporin belonging to the beta-lactamase group, effectively killing a spectrum of bacteria with the most extended half-life.…”
Section: Postoperative Prophylactic Antibioticsmentioning
confidence: 94%
“…Sensitivity resistance pattern of the microorganism at a local level of the hospital can be formed for the rational use of the antibiotics and to prevent the development of resistance. The development of effective control programs through the adoption of measures that restrict the use of specific antimicrobials, the establishment of therapeutic guidelines, the constant monitoring of the resistance pattern of the common pathogenic organisms in the hospital are recommended to improve the usage of antibiotics [16].…”
Section: As the 3 Rdmentioning
confidence: 99%